2018
DOI: 10.1111/ppc.12262
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress, coping strategies, and psychological-related outcomes of nurses working in psychiatric hospitals

Abstract: Implementing programs aimed at teaching them how to deal with stress at work and improving their coping strategies and problem-solving skills are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 57 publications
5
52
0
2
Order By: Relevance
“…Oenning et al [33] and Romswinkel et al [34] assessed job stress in general and among community-dwelling workers as opposed to employees from a specific industry which is the case for this current study. In a lower-middle-income country like Egypt, a positive correlation between work stress and depression was also reported [35]. Similar to this study, these researchers assessed both depression and occupational stress using self-reports except for Oenning et al [33] who used a diagnostic tool to measure depressive disorder.…”
Section: Discussionsupporting
confidence: 64%
“…Oenning et al [33] and Romswinkel et al [34] assessed job stress in general and among community-dwelling workers as opposed to employees from a specific industry which is the case for this current study. In a lower-middle-income country like Egypt, a positive correlation between work stress and depression was also reported [35]. Similar to this study, these researchers assessed both depression and occupational stress using self-reports except for Oenning et al [33] who used a diagnostic tool to measure depressive disorder.…”
Section: Discussionsupporting
confidence: 64%
“…3 Compared with those engaged in other areas of medicine, psychiatric nurses have been reported to perceive higher levels of stress 4 associated with difficulty in communicating with patients, repeated recurrences in many cases, and the necessity of caring for violent or aggressive patients. [5][6][7][8] Importantly, it has been reported that the incidence of patient violence/related problems in psychiatric wards is 2-to 4 -times higher than that in general wards, 9 and nearly 90% of psychiatric nurses experience such violence. [10][11][12][13][14] Based on these findings, clinical psychiatric nurses are likely to deal with violence and offensive statements daily.…”
mentioning
confidence: 99%
“…The present study showed that restorative yoga helped to alleviate stress and allowed nurses to relax when it was performed regularly for even only 5 minutes per day. Based on the report of Hasan et al and the present results, implementation of programs that teach nurses how to deal with stress at work and improve their coping strategies is recommended . Like other shift workers, nurses working the night shift may find it difficult to implement their usual stress relieving strategies due to lack of time.…”
Section: Discussionmentioning
confidence: 89%